THE RELATIONSHIP BETWEEN STRESS LEVELS AND PHYSICAL ACTIVITY WITH THE NUTRITIONAL STATUS OF FINAL STUDENTS OF THE 2021 CLASSIFICATION AT THE FACULTY OF HEALTH SCIENCES, TEUKU UMAR UNIVERSITY - Cut Nela Yulisa; Nasrianti Syam; Cukri Rahma; Ravi Masitah (PT. Radja Intercontinental Publishing, 2025)
Nutritional problems remain a significant public health challenge, encompassing both undernutrition and overnutrition, which affect quality of life and productivity. Stress levels and physical activity are factors that may influence nutritional status, particularly among final-year students who often face high academic pressure. This study aimed to analyze the relationship between stress levels and physical activity with nutritional status among final-year students of the 2021 cohort at the Faculty of Health Sciences, Teuku Umar University. This research employed an observational analytic design with a cross-sectional approach. A total of 142 respondents were selected using a simple random sampling technique from a population of 220 students. Stress levels were measured using the Depression Anxiety Stress Scale (DASS-42), physical activity using the Physical Activity Level (PAL), and nutritional status based on Body Mass Index (BMI). The data were analyzed using Spearman correlation with a significance level of p<0.05. The results showed that most respondents had normal nutritional status (64.1%), experienced severe stress (38%), and had light physical activity (35.2%). Statistical analysis revealed no significant relationship between stress levels and nutritional status (r = -0.068, p = 0.425), nor between physical activity and nutritional status (r = 0.030, p = 0.722). These findings suggest that nutritional status among students may be influenced by other factors beyond stress and physical activity. Therefore, it is recommended that students maintain healthy eating habits and balanced lifestyles despite academic pressures, while further research should explore additional determinants of student nutritional status.